PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TINGKAT SUKU BUNGA TERHADAP PROFITABILITAS PERUSAHAAN FOOD AND BEVERAGE YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2011-2018 - Tama, Senna Dio; Effendi, Maya Syafriana (IKRA-ITH EKONOMIKA, 2019)
The research aim to finds out the influence of Current Ratio, Debt to Equity Ratio, andInterest Rate Level towards Profitability in Food and Beverage companies listed on IndonesiaStock Exchange 2011-2018 period. The data used in this study was obtained from AnnualFinancial Statements Food and Beverage companies listed on Indonesia Stock Exchange. Afterpassing through the stage of purposive sampling, the samples are fit for use by 9 companies.The analysis method used the analysis of panel data regression fixed effect model with Eviewsprogram ver 9.0.The results from this research show that Current Ratio partially affected Profitabilitypositive and significantly, Debt to Equity Ratio partially affected Profitability negative andsignificantly, and Interest Rate Level also affected Profitability negative and significantly.Result from Adjusted R-square on regression model was at 0.8851. The research shows thatcontribution of independent variabels, Current Ratio, Debt to Equity Ratio, and Interest RateLevel are affecting Profitability at 88.51%. The rest of the 11.49% consist of variables outsideof those that were used in this research.